Health and nutrition: Overview - Quisumbing, Agnes R. (International Food Policy Research Institute, 2003)
Gender differences in health and nutrition have long been a subject of study in the intrahousehold allocation literature. Unlike consumption expenditures or farm production, measurements of health and nutritional outcomes are always at the individual level, and thus factors that underlie systematic differences in outcomes—such as age, gender, and position within the household—are more readily apparent.